Elevated Factor VIII and von Willebrand Factor Levels Predict Unfavorable Outcome in Stroke Patients Treated with Intravenous Thrombolysis - Tóth, Noémi Klára; Székely, Edina Gabriella; Czuriga-Kovács, Katalin Réka; Sarkady, Ferenc; Nagy, Orsolya; Lánczi, Levente István; Berényi, Ervin; Fekete, Klára; Fekete, István; Csiba, László; Bagoly, Zsuzsa (Frontiers in Neurology, 2018)
Introduction: Plasma factor VIII (FVIII) and von Willebrand factor (VWF) levels have been associated with the rate and severity of arterial thrombus formation and have been linked to outcomes following thrombolytic therapy in acute myocardial infarction patients. Here we aimed to investigate FVIII and VWF levels during the course of thrombolysis in acute ischemic stroke (AIS) patients and to find out whether they predict long-term outcomes. Materials and methods: Study population included 131 consecutive AIS patients (median age: 69 years, 60.3% men) who underwent i.v. thrombolysis with recombinant tissue plasminogen activator (rt-PA). Blood samples were taken on admission, 1 h and 24 h after rt-PA administration to measure FVIII activity and VWF antigen levels. Neurological deficit of patients was determined according to the National Institutes of Health Stroke Scale (NIHSS). ASPECT scores were assessed using CT images taken before and 24 h after thrombolysis. Intracranial hemorrhage was classified according to the ECASS II criteria. Long-term functional outcome was determined at 90 days after the event by the modified Rankin scale (mRS). Results: VWF levels on admission were significantly elevated in case of more severe AIS (median and IQR values: NIHSS<6:189.6% (151.9-233.2%); NIHSS 6-16: 199.6% (176.4-250.8%); NIHSS>16: 247.8% (199.9-353.8%), p=0.013); similar, but non-significant trend was observed for FVIII levels. FVIII and VWF levels correlated well on admission (r=0.748, p<0.001) but no significant correlation was found immediately after thrombolysis (r=0.093, p=0.299), most probably due to plasmin-mediated FVIII degradation. VWF levels at all investigated occasions and FVIII activity before and 24 h after thrombolysis were associated with worse 24 h post-lysis ASPECT scores. In a binary backward logistic regression analysis including age, gender, hsCRP, active smoking, diabetes and NIHSS>5 on admission, elevated FVIII and VWF levels after thrombolysis were independently associated with poor functional outcomes (mRS≥3) at 90 days (immediately after thrombolysis: FVIII: OR: 7.10, 95%CI:1.77-28.38, p=0.006, VWF: OR:6.31, 95%CI:1.83-21.73, p=0.003; 24 h after thrombolysis: FVIII: OR:4.67, 95%CI:1.42-15.38, p=0.011, VWF: OR:19.02, 95%CI:1.94-186.99, p=0.012). Conclusions: Elevated FVIII activity and VWF antigen levels immediately after lysis and at 24 h post-therapy were shown to have independent prognostic values regarding poor functional outcomes at 90 days.